Academic Performance of Students with Hearing Impairments: A Study in Post-Primary Special Education - Kanwal, Asma; Bashir, Rukhsana; Qaisar, Sana (Annals of Human and Social Sciences, 2024)
The study investigates the academic achievement of students with hearing impairments in English, Urdu, and Mathematics after completing a five-year primary special education program in Punjab's public sector. Students with hearing impairments often face academic challenges, highlighting the need for evaluations to guide targeted educational interventions. A descriptive cross-sectional design with a quantitative approach was used. A sample of 56 students, selected through simple random sampling, was assessed using curriculum-aligned tests in English, Urdu, and Mathematics. Data were analyzed using descriptive and inferential techniques, with scores categorized into below average, average, and above-average levels. Most students scored below average in reading, writing, and numeracy. A significant gender difference was found in the Urdu Written Test (p = .013). No significant differences were noted for other demographic variables. Educational institutions should implement tailored interventions to address the specific needs of students with hearing impairments to improve their academic outcomes.